Elderly aortic stenosis patients' perspectives on treatment goals in transcatheter aortic valvular replacement. (8th June 2022) - Sugiura, Kohei; Kohno, Takashi; Hayashida, Kentaro; Fujisawa, Daisuke; Kitakata, Hiroki; Nakano, Naomi; Saito, Tetsuya; Hase, Hiromu; Yoshijima, Nobuhiro; Tsuruta, Hikaru; Itabashi, Yuji; Kohsaka, Shun; et al.
Abstract: Aims: Transcatheter aortic valvular replacement (TAVR) is increasingly being performed for elderly patients with aortic stenosis (AS), and current guidelines acknowledge the importance of shared decision‐making in their management. This study aimed to evaluate elderly symptomatic severe AS patients' perspectives on their treatment goals and identify factors that influence their treatment choice. Methods and Results: We performed a pre‐procedural cross‐sectional survey using a questionnaire at a single university hospital. The questionnaire included three primary domains: (i) symptom burden, (ii) goals and important factors related to treatment, and (iii) preferred place of residence after treatment. We investigated 98 symptomatic severe AS patients who underwent TAVR (median age 86 years, 26% men). None of the patients died during hospitalization, and most of them (94%) were discharged home. Prior to TAVR, the three most common symptom burdens were poor mobility (52%), shortness of breath (52%), and weakness (44%). The reported preferred treatment goals were symptom burden reduction (78%), independence maintenance (68%), ability to perform a specific activity/hobby (62%), and improvement in prognosis (58%). In total, 54% of the patients rated 'in alignment with my values' as the factor that affected their decision to undergo TAVR. Nearly all patients (95%) stated that they preferred to live at home after TAVR. Conclusions: Among elderly AS patients with varying symptoms who underwent TAVR, symptom burden reduction was the most cited patient‐reported goal. Nearly all the patients preferred to live at home after the procedure. Encouraging patients to define their specific goals may improve the quality of shared decision‐making in such settings.